Can China’s national fitness policy contribute to achieving universal health? Analysis based on the three-dimensional framework - Dong, Defeng; He, Bing; Kong, Jianda; Zhou, Aitong; Lv, Mei; Zhang, Dianbo; Dong, Chen (Frontiers in Public Health, 2025)
IntroductionA lack of physical activity is widely regarded as an important factor contributing to the increase in non-communicable diseases and mortality rates. To improve the physical fitness and health levels of its citizens, the Chinese government has launched the National Fitness Program (NFP) to promote public health and well-being. However, the mechanisms and performance of these policies in promoting public health still require further exploration.MethodsThis paper conducts a systematic analysis and evaluation of the NFP from 1995 to 2025 from three dimensions: policy themes, policy tools, and policy consistency, using text analysis, content analysis, and the Policy Modeling Consistency (PMC) model.Results and conclusionThe results show that the core themes of the NFP focus on infrastructure development, mass sports activities, and the public health service system. In terms of policy tools, there is an overall structural imbalance and internal disarray, with environmental policy tools dominating, supplemented by supply-side policies, while demand-side policies are insufficient. The level of policy consistency is good, and the design is relatively scientific and reasonable. However, there are significant differences between policies, and some indicators need improvement. Therefore, we recommend: enhancing cross-departmental, cross-disciplinary, and cross-regional cooperation, emphasizing evidence-based decision-making; promoting the balanced development of national fitness, increasing the inclusivity of policies, and focusing on the rights of special groups; Increasing incentive measures to encourage social participation; increasing the use of demand-oriented policy tools; improving the policy evaluation system to achieve dynamic optimization of policies.